2005
DOI: 10.1093/toxsci/kfi116
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Gene Expression Profiles of Dioxin Exposure in Zebrafish Embryos

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a widespread environmental contaminant that causes altered heart morphology, circulatory impairment, edema, hemorrhage, and early life stage mortality in fish. TCDD toxicity is dependent, in large part, on the aryl hydrocarbon receptor (AHR), but understanding of the molecular mechanism of cardiovascular embryotoxicity remains incomplete. To identify genes potentially involved in cardiovascular effects, we constructed custom cDNA microarrays consisting of 4896 zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 47 publications
4
75
0
Order By: Relevance
“…Gene knockdown continues well into the larval stage, as seen in zebrafish. One additional point to note with regard to morpholino duration is that the gene we selected for evaluation of MO technologies in Fundulus (CYP1A) is highly inducible (Handley-Goldstone et al, 2005;Timme-Laragy et al, 2007). As such, it provides a very rigorous test of the duration of morpholino action.…”
Section: Discussionmentioning
confidence: 99%
“…Gene knockdown continues well into the larval stage, as seen in zebrafish. One additional point to note with regard to morpholino duration is that the gene we selected for evaluation of MO technologies in Fundulus (CYP1A) is highly inducible (Handley-Goldstone et al, 2005;Timme-Laragy et al, 2007). As such, it provides a very rigorous test of the duration of morpholino action.…”
Section: Discussionmentioning
confidence: 99%
“…Heart was also identified as the primary site of AHR2β expression. Several studies have identified the heart as a principal target organ for TCDD toxicity in fishes, resulting in altered gene expression and cardiovascular impairments (Carney et al 2006;Handley-Goldstone et al 2005;Hornung et al 1999;Spitsbergen et al 1991). The expression of all four salmon AHR2 forms in heart could indicate that this organ is at higher risk of toxicity after TCDD exposure.…”
Section: Discussionmentioning
confidence: 99%
“…They are groups that may have large and divergent downstream effects, and an early response to AhR agonists is typically seen in genes belonging to these GO groups (Fletcher et al, 2005,Handley-Goldstone et al, 2005,Carney et al, 2006. Furthermore, the effect of AhR agonists on multiple signaling cascades is consistent with previous transcriptomic studies in the early life stages of zebrafish (Handley-Goldstone et al, 2005,Carney et al, 2006.…”
Section: Signal Transduction and Transcriptionmentioning
confidence: 99%